Gambaran Penanganan Sampah Kelapa Muda di Pantai Padang dan Pembuatan Cocopeat Tahun 2024 - Azzhara, Dinda; Mahaza, Mahaza; Irmawartini, Irmawartini; Riviwanto, Muchsin; Gusti, Awalia (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2024)
The abundance of green coconut aste around Padang beaches increases every day, causing waste generation to become a factor that affects the environment and health. Many young coconut traders along the coast of Padang do not pay attention to handling and what is produced. There are no young coconut traders along the Padang coast who use young coconut waste. The aim of this research is to find out an overview of the handling of young coconut waste along the Padang coast and the production of cocopeat. This type of research is descriptive, namely describing the handling of young coconut waste along the Padang coast and the manufacture of cocopeat. Data analysis was carried out using a univariate method. The results of the study stated that the average generation of young coconut waste along Padang Beach was 10.8 kg/unit/day. Waste sorting in the good category (18.2%) and bad category (81.8%). Waste containers in the bad category (100%). and young coconut waste is used as cocopeat. For handling young coconut waste, it is hoped that young coconut traders along the coast of Padang will be able to pay attention to the generation of young coconut waste that is produced every day. Pay attention to the container for young coconut waste. Utilizing young coconut waste into something useful.